Knowledge Management for Strengthening Human Resource-Based Mosque Economies - Syahputra, Hendra; Kamal, Syafruddin; Rizqy, Irhas; Rusdi, Muhammad; Ilyas, Fithriady (Share: Jurnal Ekonomi dan Keuangan Islam, 2025)
The Covid-19 pandemic has disrupted human resource management in religious institutions, exposing gaps in knowledge and the absence of effective mosque-based economic empowerment models. This study aims to examine the influence of knowledge management (KM) on strengthening the human resource-based economy of mosques in Aceh under dynamic socio-economic conditions. A quantitative approach was applied, involving 250 mosque administrators from 23 districts and cities in Aceh, selected through proportional stratified random sampling. Data were analyzed using Structural Equation Modelling (SEM) with LISREL 8.80. The findings reveal that KM exerts a positive and significant effect on human resource-based economic strengthening, with satisfaction emerging as the most influential indicator, followed by efficiency, effectiveness, and innovation. The study contributes to the literature by developing an evidence-based KM framework for religious institutions and offers practical insights for policymakers to enhance mosque governance. Recommended strategies include establishing an integrated KM system, expanding digital capabilities, and fostering inter-mosque learning networks to optimize human resource potential. Abstrak Manajemen Pengetahuan untuk Penguatan Ekonomi Masjid Berbasis Sumber Daya Manusia.  Pandemi Covid-19 telah mengganggu manajemen sumber daya manusia di lembaga keagamaan, mengungkap adanya kesenjangan pengetahuan dan ketiadaan model pemberdayaan ekonomi berbasis masjid yang efektif. Penelitian ini bertujuan untuk menguji pengaruh manajemen pengetahuan (KM) terhadap penguatan ekonomi berbasis sumber daya manusia di masjid-masjid Aceh dalam kondisi sosial-ekonomi yang dinamis. Pendekatan kuantitatif digunakan dengan melibatkan 250 pengurus masjid dari 23 kabupaten/kota di Aceh yang dipilih melalui teknik proportional stratified random sampling. Data dianalisis menggunakan Structural Equation Modelling (SEM) dengan LISREL 8.80. Hasil penelitian menunjukkan bahwa KM berpengaruh positif dan signifikan terhadap penguatan ekonomi berbasis sumber daya manusia, dengan kepuasan sebagai indikator paling berpengaruh, diikuti efisiensi, efektivitas, dan inovasi. Studi ini memberikan kontribusi terhadap pengembangan kerangka KM berbasis bukti untuk lembaga keagamaan dan menawarkan wawasan praktis bagi pembuat kebijakan dalam meningkatkan tata kelola masjid. Strategi yang direkomendasikan meliputi pembentukan sistem KM terintegrasi, penguatan kapasitas digital, dan pengembangan jaringan pembelajaran antar masjid untuk mengoptimalkan potensi sumber daya manusia.